Evaluating urban heat island intensity and its associated determinants of towns and cities continuum in the Yangtze River Delta Urban Agglomerations. (October 2019) - Sun, Yanwei; Gao, Chao; Li, Jialin; Wang, Run; Liu, Jian
Highlights: ATC model was used to reconstruct the MODIS 8-day LST data. UHI existed extensively in most of the towns and cities over the YRDUA region. Urban cluster size and perimeter were the relatively important variables to explain the variations of UHII. The LST difference between urban and rural areas increased with urban expansion. Abstract: Urban heat island (UHI) is known as a main environmental problem within urban agglomerations due to its associated urban growth, human mobility and socioeconomic expansion. The UHI intensity (UHII) generally varies with the changes in the urban size. Although numerous researches have highlighted the monitoring and quantification of the spatial-temporal dynamics characteristics of UHI effects in larger-scale central cities, there is still limited understanding regarding variations in the UHI effects over smaller human settlements (e.g., towns). This study aims to fill this gap by considering the towns and cities as a continuum to examine the inner-annual dynamics of the UHII and its various determinants within the Yangtze River Delta Urban Agglomerations (YRDUA). To investigate the changes in the land surface temperature (LST), we utilized an annual temperature cycle (ATC) model to reconstruct the MODIS 8-day LST data with a 1 km 2 resolution in 2015. The results showed that a UHI existed extensively in most of the towns and cities over the YRDUA region during the time. The mean UHII in the summer months was greater than that during the winter, while the nighttime value was lower than that during the daytime. The LST difference between urban and rural areas increased with urban expansion. Compared with the other influencing factors, urban cluster size and the perimeter of urban extent polygon were the relatively important variables to explain the variations in the UHII. This empirical study could provide useful information to mitigate the UHI of towns and cities continuum through top-level design and land-use planning of urban agglomerations.